Analysis of the Effectiveness of Regional Inspectorates in Performing Oversight Functions: A Focus on Responsiveness and Accountability - Kurniawan, Kurniawan; juminarni, Aryuni; Salida, Amrizal; Haeril, Haeril; Fadlina, Fadlina (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2024)
This study aims to analyze the effectiveness of the 1focusing on aspects of responsiveness and accountability. This research employs a descriptive qualitative method with a case study approach. The study population includes all employees of the Inspectorate and Regional Government Organizations (OPD) in Sidenreng Rappang Regency, with the sample selected using purposive sampling techniques. The findings indicate that the effectiveness of the Sidenreng Rappang Inspectorate's oversight has been well-executed, demonstrated through indicators of responsiveness such as the ability to respond to the public, speed, accuracy, timeliness in service, and complaint handling. The accountability aspect is also proven effective based on the Government Agency Performance Report (LKjIP), which serves as a reference in achieving the Inspectorate's vision and mission, as well as the preparation of performance-based accountability reports. However, the study also identified several challenges, including limited human resources and the lack of public dissemination of oversight documents. These results explain that the Sidenreng Rappang Regency Inspectorate is effective in its role as an internal supervisor, transitioning from its initial function as a watchdog to now functioning as a mentor, consultant, early warning system, and quality assurance. However, continuous efforts are needed to enhance capacity and oversight effectiveness to support better governance.